Implementation of Environmental Arrangement in The Merdeka Curriculum at The Halimatusadiah Paud Unit in Jambi City - Harlina; Priyanti, Nita (Kirana Publisher (KNPub), 2024)
The arrangement of the play environment for early childhood can basically influence the way they learn and encourage to explore creativity since early stage. For That, the need for a management the good and conducive for children's play environments, one of which is by implementing the latest curriculum model, namely independent learning. This study aims to analyze the Implementation of Play Environment Arrangement in the Merdeka Curriculum in the Halimatusadiah PAUD Unit. The research method used is qualitative descriptive study. Subjects The research participants were 1 homeroom teacher and students at PAUD Halimatusadiah, as well as the head of the institution. education. Data Which collected by researcher through interview, observation and documentation. Results This study shows that there are various types of APE provided in schools for organizing activities. play Which different every the week, Good in form project or center play in the classroom. Media The learning used is APE loose parts and also the use of used goods and natural materials. Impact implementation This that is in implementation use arrangement environment Independent Study giving children the freedom to be able to create their own critical thinking skills in their work, without create atmosphere Study monotonous.